Food and drink advertising along school children’s transport routes in Victoria, Australia and policy implications - Sherly X Li; Claire Hardi; Rebecca Godwin; Rachael Jinnette; Belinda Morley; Helen Dixon; Jane Martin (Public Health Nutrition)
Abstract